Pengaruh Motivasi Belajar dan Disiplin Belajar Terhadap Hasil Belajar Siswa pada Mata Pelajaran Ekonomi Kelas XI SMA Negeri 5 Pematangsiantar T.A 2025/2026: Penelitian - Putri Sahayu Sinaga; Sotarduga Sihombing; Benjamin Albert Simamora (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effect of learning motivation and discipline on student learning outcomes in Economics for Grade XI students at SMA Negeri 5 Pematangsiantar, Academic Year 2025/2026. This research is quantitative and uses descriptive methods. The study population comprised 11 classes with 178 students. Sampling was conducted using proportional random sampling, resulting in a sample size of 64 students. Data were collected through questionnaires for the variables of learning motivation and learning discipline, as well as tests as indicators of learning outcomes in economics subjects. Data analysis techniques used include simple linear regression tests, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results of the analysis show that there is a positive and significant influence of learning motivation on student learning outcomes with (t count = 2.195> t table = 1.669) and there is a positive and significant influence of learning motivation on student learning outcomes with (t count = 1.784> t table = 1.669). The results of the F test show that simultaneously both variables have a significant effect on student learning outcomes (F count = 9.2> F table = 3.15). The coefficient of determination (R²) value of 0.429 indicates that 42.9% of the variation in student learning outcomes is influenced by learning motivation and learning discipline, while the remaining 57.1% is influenced by other factors not examined in this study.